Fission yeast cells deficient in siderophore biosynthesis require Str2 for ferrichrome-dependent growth - Mbuya, Berthy; Plante, Samuel; Vahsen, Tobias; Brault, Ariane; Labbé, Simon (Frontiers in Microbiology, 2025)
Ferrichrome (Fc) acquisition in Schizosaccharomyces pombe is mediated by the cell-surface siderophore-iron transporter Str1. Here, we report that Str2, a protein homologous to Str1, localizes to the vacuolar membrane. Like Str1, Str2 expression is transcriptionally regulated in response to changes in iron concentrations. Both the str2+ and str1+ genes are induced under low-iron conditions and are repressed by the iron-responsive GATA-type transcription factor Fep1 when iron is abundant. Under high-iron conditions, chromatin immunoprecipitation (ChIP) assays reveal that TAP-Fep1 occupies the str2+ and str1+ promoters. Isolated vacuoles from str2Δ fep1Δ cells expressing GFP-tagged Str2 exhibit iron accumulation in vacuoles upon exposure to exogenous holo-Fc. sib1Δ sib2Δ cells deficient in Fc biosynthesis and lacking the str2+ gene (str2Δ) are unable to grow in the presence of exogenous Fc as a sole source of iron. Further analysis identified that conserved amino acids Tyr539 and Tyr553 in the last predicted loop of Str2 are required for supporting Fc-dependent growth of a sib1Δ sib2Δ mutant strain. Collectively, these findings indicate that the vacuolar Str2 protein plays a role in the consumption of Fc as an iron source, while also revealing the involvement of the vacuole in iron release from exogenous Fc after its assimilation.